Transisi Ekonomi Wilayah Kabupaten di Jawa Tengah dan Keterkaitannya dengan Perkembangan Ekonomi Lokalnya - Nisa Ayunda Adni; Jawoto Sih Setyono (Teknik PWK (Perencanaan Wilayah Kota), 2016)
Central Java economic development has been dynamic and diverse. The economy of the region has grown gradually and experienced structural transition. The regional economy which was originally based on the primary sector has transformed to a more modern one which the secondary and tertiary sectors start to dominate the economy. While the growth of the regional economy is widely believed to be caused mainly by exogenous factors, there has been tendency the emergence of local economic factors. This research aims to examine the possible relationship between economic transition and the persistence of local economic development factors among districts in Central Java. This study applies quantitative descriptive analysis combining the methods of scoring analysis, weighted analysis and correlation analysis together to explore the relationship. The research shows that in general there is positive relationship between economic growth and local economic development indicators. This result can contribute to fostering local factors as part of regional and local economic development policies for the region.